2012
DOI: 10.1080/08952841.2012.638875
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine For Physical Performance, Energy, Immune Function, and General Health Among Older Women and Men in the United States

Abstract: We examined use of complementary and alternative medicine (CAM) for health and well-being by older women and men. Data were from the 2007 National Health Interview Survey, representing 89.5 million Americans ages 50+. Multivariate logistic regression accounted for the survey design. For general health, 52 million people used CAM. The numbers for immune function, physical performance, and energy were 21.6, 15.9, and 10.1 million respectively. In adjusted results, women were much more likely than men to use CAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…Our findings are consistent with other studies regarding the relationship of CAM use to gender, 21 race, 22 and education. 23 It is also not surprising that lower income patients reported more use of topical agents and wealthier participants reported more use of manipulative and body-based therapies, given the difference in cost between these therapies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with other studies regarding the relationship of CAM use to gender, 21 race, 22 and education. 23 It is also not surprising that lower income patients reported more use of topical agents and wealthier participants reported more use of manipulative and body-based therapies, given the difference in cost between these therapies.…”
Section: Discussionsupporting
confidence: 93%
“…Women, 21 Non-Hispanic White, 22 higher income or education 23 and having insurance coverage 24 have been correlated with increased CAM use in cross-sectional studies. We measured income as the personal family income for the last year, including all sources such as wages, salaries, social security and retirement benefits.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the United States has seen an upward trend in the use of nonconventional medicine for chronic conditions, [19][20][21][22] mimicking trends seen internationally. [23][24][25] Although many studies have examined the use of complementary and alternative medicine (CAM) within different chronic disease populations, 16,26,27 researchers also suggest that the reasons for CAM use for chronic back or neck pain and other musculoskeletal diseases warrant further study.…”
Section: Introductionmentioning
confidence: 90%
“…Collectively, the results for the predisposing, enabling, and need factors were consistent with previous research on the use of CAM, including supplement use. 32,44,48,52 Adults who reported that their health was now better than last year were more likely to have used supplements for cognitive health than those who said their health was the same. While this result may suggest an association between supplement use and improved general health, the study design and the characteristics of our data suggest caution regarding that interpretation.…”
Section: Discussionmentioning
confidence: 94%
“…Developed to study factors that contribute to the use of acute care health services, the Andersen model has been applied to use of CAM, including supplements. 44 48 The model suggests that supplement use is determined by 3 sets of factors: predisposing factors, enabling factors, and need factors. 43 Predisposing factors measured in the present analysis were gender, age, marital status, ethnicity, and education.…”
Section: Methodsmentioning
confidence: 99%